Qorpo-Santo, encenador de si mesmo - Santos, Thiago de Freitas (2012)
In 1877 José Joaquim de Campos Leão Qorpo-Santo privately printed, with the exception of one of the nine volumes, his complete work, the Ensiqlopédia ou Seis mezes de huma enfermidade.The construction of the encyclopedia project reveals at times a troubled process of creation, as if the author had a race against time, with no possible corrections, sometimes in an uninterrupted flow. The theater, for example, all of it dated, was written in only six months, from January to June 1866. This work revolves around of how Qorpo-Santo produced a theatre that demonstrates all the time its artificial nature, either by his self-representation, conscious characters, or the play within the play. We also discussed the concept of openwork, and highlighted the “opening” that Qorpo-Santo gives to the reader. A freedom of speech that comes from self-consciousness,that his work is incomplete, perhaps even imperfect. Ironically, the playwright titled his work Ensiqlopédia(encyclopedia), suggesting universality. However, what takes place is a theatrefull of imperfections, not aesthetics, but as reflect of the human condition, a chaotic and fragmented world.